2022
DOI: 10.3389/fcell.2022.818457
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Ferroptosis-Related Prognostic Signature for Melanoma Based on Single-Cell RNA Sequencing

Abstract: Melanoma, the deadliest type of skin cancer, is on the rise globally. The generally poor prognosis makes melanoma still an enormous public health problem. Ferroptosis is a newly emerging form of iron-dependent regulated cell death, which has been implicated in the development and treatment of several tumors. However, whether there is a connection between ferroptosis-related genes and the prognosis of melanoma patients remains an enigma. In the present study, we identified a ferroptosis-related genes signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 98 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…Evaluation of the prognostic value of ferroptosis regulated genes has been widely conducted in diverse tumors, such as melanoma, clear cell renal cell carcinoma, breast cancer, lung adenocarcinoma, hepatocellular carcinoma, and so on ( Liang et al, 2020 ; Jin et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Ping et al, 2022 ). The correlation between ferroptosis regulators and immune signatures has also been explored in different tumors, including melanoma ( Fan et al, 2021 ; Wang et al, 2021 ; Liu et al, 2022 ). Dividing tumor patients into subgroups based on their molecular signatures, such as ferroptosis-related gene signatures, enable us to predict their diverse phenotypes, treatment response, and prognosis ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the prognostic value of ferroptosis regulated genes has been widely conducted in diverse tumors, such as melanoma, clear cell renal cell carcinoma, breast cancer, lung adenocarcinoma, hepatocellular carcinoma, and so on ( Liang et al, 2020 ; Jin et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Ping et al, 2022 ). The correlation between ferroptosis regulators and immune signatures has also been explored in different tumors, including melanoma ( Fan et al, 2021 ; Wang et al, 2021 ; Liu et al, 2022 ). Dividing tumor patients into subgroups based on their molecular signatures, such as ferroptosis-related gene signatures, enable us to predict their diverse phenotypes, treatment response, and prognosis ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies exploring prognostic gene models related to ferroptosis in tumors. Liu et al identified the prognostic significance of ferroptosis-related genes (FRGs) in melanoma, and proposed a novel four-gene prognostic signature that may impact the assessment and clinical decision making for melanoma patients [ 23 ]. A recent study suggested a 10-biomarker signature that could be clinically used to predict the prognosis of cutaneous melanoma [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ferroptosis has provided innovative insights into the development of effective combination therapies and synergistic strategies for cancer treatments [ 10 12 ]. According to previous reports, melanoma is potentially more susceptible to ferroptosis than other tumors, which stems from the higher levels of dissociative iron in melanoma cells [ 13 ], revealing the bright prospect of ferroptosis in developing innovative strategies for melanoma therapy. Nevertheless, there is still a lack of stable and valid ferroptosis inducers, highlighting the need for further optimization of novel nanomaterials to activate ferroptosis.…”
Section: Introductionmentioning
confidence: 99%